Kinship System and Its Influence on Islamic Inheritance Law in Indonesia - Turnip, Ibnu Radwan Siddik; Ningsih, Suria; Nurhayati, Nurhayati; Lubis, Risyad Fakar (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Kinship system known to indigenous peoples in Indonesia is divided into three parts namely patrilineal, matrilineal and parental system. Each tribe in Indonesia has its own inheritance system that is influenced by the kinship system, while on the other hand the indigenous people have also embraced Islam which of course should follow the pattern of Islamic inheritance. This paper will try to examine whether this kinship system still affects the resolution of the issue of inheritance for those who are already Muslims and whether this kinship system also affects the provisions of Islamic inheritance in Indonesia. This research is qualitative research using legal anthropological approach. The results showed that this kinship system still has an effect on the completion of inheritance in indigenous Islamic peoples in Indonesia such as Karo, Minangkabau and Javanese Islamic communities. In the development of Islamic inheritance in Indonesia, efforts to make the bilateral inheritance system are seen in some of the articles on the Compilation of Islamic Law (KHI) supported by Islamic law reformers in Indonesia.